Canola meal in cattle rations - VALERGAKIS (Γ. Ε. ΒΑΛΕΡΓΑΚΗΣ) G. E.; OIKONOMOU (Γ. ΟΙΚΟΝΌΜΟΥ) G. (Journal of the Hellenic Veterinary Medical Society, 2017)
European Union’s policy to promote the production of "bio-fuel" from "energy plants" creates a favourable perspective for rapeseed production in Greece. Rapeseed oil is used to produce "bio-diesel" and after its extraction, a high-protein meal results. Greece is a net importer of protein feeds, which means that a great opportunity arises for the local animal industry. It must be noted that the varieties of rapeseed that are currently used ("canola" or "double zero") contain only minimum amounts of the toxic factors (erucic acid and glucosinolates) of older varieties. In this study, we present: a) the oil extraction method which can affect the quality of canola meal, b) the chemical composition, the nutritive value and the qualitative characteristics of canola meal’s nitrogen fraction, c) the use of canola meal in cattle rations and the productivity of cattle receiving these rations and d) the results of a simulation concerning the use and the profitability of canola meal under Greek conditions. Canola meal has a lower nutritional value compared to soybean meal, but not compared to cottonseed and sunflower meals. It presents some interesting features, namely a high methionine, calcium and phosphorus content and significant amounts can be included in balanced cattle rations (15-20% of dry matter), without any negative effect on feed consumption or animal productivity. Canola meal use in cattle rations is profitable when its price is less than 70-75% ofthat of soybean meal.